Metode Importance Performa Analisys (IPA) sebagai Penentuan Kepuasan dan Kenyamanan Pengguna Website Universitas PGRI Madiun - Fatim Nugrahanti; Kelik Sussolaikah (LPPM STIKOM Dinamika Bangsa, 2021)
PGRI Madiun University is an institution in the city of Madiun in its development using the website as a tool to promote. Today's technology is very advanced and has many benefits for life in our environment. Website is an effective promotional media, providing information and receiving information speed is very fast. Therefore, PGRI Madiun University uses the website for promotional purposes in addition to academic activities so far. Correct and accurate information will have an impact on society, and the trust given to the community will also increase. Analysis of the quality of use and utilization of the website to see visitor satisfaction with information and services when viewed from user satisfaction is needed to measure user satisfaction. This study analyzes how much user satisfaction is with the university website using the Importance Performance Analysis (IPA) approach. The results of the Importance Performance Analysis (IPA) analysis show that several recommendations are obtained from the results of the analysis of this research which are the priority and the main thing to be maintained is the quality of information. So that visitors feel faster and more accurate in obtaining information with the PGRI Madiun University website. Keywords: Website. Importance Performance Analysis, Analysis.